The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.rmed.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of sarcoidosis associated pulmonary hypertension: Results of a multi-national registry

Abstract: The clinical features of SAPH were similar across multiple centers in the US, Europe, and the Middle East. The severity of SAPH was related to reduced DLCO. There were treatment differences between the US and non-US centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 24 publications
2
52
1
2
Order By: Relevance
“…Forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and DLCO are generally lower in SAPH compared with sarcoidosis patients without PH. 6,7,11,18,21,60 DLCO seems to be the strongest independent predictor. 18,21 As mentioned earlier, destruction of the alveoli and loss of pulmonary capillary volume due to fibrosis and muscle cell proliferation are believed to cause reduction of the DLCO.…”
Section: Pulmonary Function Testsmentioning
confidence: 87%
See 2 more Smart Citations
“…Forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and DLCO are generally lower in SAPH compared with sarcoidosis patients without PH. 6,7,11,18,21,60 DLCO seems to be the strongest independent predictor. 18,21 As mentioned earlier, destruction of the alveoli and loss of pulmonary capillary volume due to fibrosis and muscle cell proliferation are believed to cause reduction of the DLCO.…”
Section: Pulmonary Function Testsmentioning
confidence: 87%
“…7,16 There is no consensus about female/male predominance in SAPH, and seems to vary in different ethnicities. 8,17,18…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…103 Two recent large registries have reported on SAPH in France, the United States, Europe, and Middle East. 95,105 These two registries found that many patients had moderate-to-severe pulmonary hypertension. Most patients were treated with vasodilator therapy.…”
Section: Therapymentioning
confidence: 99%
“…Pulmonary hypertension (PH) is a well-recognised complication of several ILDs, worsening prognosis and impairing exercise capacity [3][4][5][6][7][8]. Among patients with ILD, PH has been most often studied in IPF, sarcoidosis and hypersensitivity pneumonitis [9][10][11]. The prevalence of PH ranges from 8 up to 86% in patients with IPF, and from 6 up to 74% in patients with sarcoidosis-depending on the diagnostic algorithm, the PH definition, the stage and severity of the underlying disease [4,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%